2013
DOI: 10.1111/iju.12115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of severity and duration of bladder outlet obstruction on catalase and superoxide dismutase activity

Abstract: Abbreviations & AcronymsObjectives: To study the effects of partial bladder outlet obstruction on the cell's anti-oxidant defense mechanisms, superoxide dismutase and catalase, in order to elucidate how the bladder responds to oxidative stress. Methods: Four groups of eight rabbits were subjected to partial bladder outlet obstruction for 4, 8 and 12 weeks. Eight sham rabbits were used as the control group. The bladders were removed under anesthesia, and the muscle and mucosa were separated, frozen and stored a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The activities of redox status markers (total SOD, GSH-Px, and CAT) were also measured. We found that the activities of these markers were significantly decreased in the bladder of the BOO group compared to the sham group; however, SFN significantly enhanced their activities in BOO rats, which is consistent with other literature [ 18 ]. These results suggested that SFN could alleviate oxidative stress by increasing the activities of antioxidative enzymes in BOO rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The activities of redox status markers (total SOD, GSH-Px, and CAT) were also measured. We found that the activities of these markers were significantly decreased in the bladder of the BOO group compared to the sham group; however, SFN significantly enhanced their activities in BOO rats, which is consistent with other literature [ 18 ]. These results suggested that SFN could alleviate oxidative stress by increasing the activities of antioxidative enzymes in BOO rats.…”
Section: Discussionsupporting
confidence: 92%
“…The oxidative stress marker was conducted as previously described [ 17 , 18 ]. The content of MDA, GSH-Px, total SOD, and CAT in the bladder tissues was measured by spectrophotometry according to the manufacturer's protocols.…”
Section: Methodsmentioning
confidence: 99%
“…SOD is one of the major antioxidant enzymes that protect the male reproductive organs against the harmful effects of ROS [27]. Hydrogen peroxide (H 2 O 2 ) , less effective than the superoxide group, is neutralized by being converted into products with a weaker effect, such as water and oxygen, by enzymes present in tissue, such as catalase and glutathione [28]. We investigated whether the antioxidant enzymes SOD and CAT have a protective effect that eliminates free radicals forming with MTX.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that PBOO significantly increased a variety of oxidative stress factors, including the levels of 8‐hydroxy‐2′‐deoxyguanosine (8‐OHdG) in the urine, plasma, and bladder tissue and the level of malondialdehyde (MDA) in plasma . In contrast, the activity of both superoxide dismutase and catalase in the bladder is decreased after obstruction, suggesting that PBOO compromises the antioxidative capacity of the tissue . Various animal models of PBOO indicate that PBOO is intimately associated with inflammation and oxidative stress, implying a critical role of the systemic immune response in the pathogenesis of PBOO .…”
Section: Introductionmentioning
confidence: 99%
“…4 In contrast, the activity of both superoxide dismutase and catalase in the bladder is decreased after obstruction, suggesting that PBOO compromises the antioxidative capacity of the tissue. 5 Various animal models of PBOO indicate that PBOO is intimately associated with inflammation and oxidative stress, implying a critical role of the systemic immune response in the pathogenesis of PBOO. 6,7 In addition, another study demonstrated a transient, reversible increase in the levels of circulating myeloid-derived suppressor cells (MDSCs), interleukin (IL)-10, and interferon (IFN)-γ in a rat model of PBOO.…”
Section: Introductionmentioning
confidence: 99%